You are not logged in.

Go back

thanks.

I do not think so.a+bi=c+diimpliesa-c=(b-d)*iIf (b-d)!=0, then a-c is complex, which is not possible. So, b-d must be equal to 0, i.e. b must equal d. That further implies that a-c=0, i.e. a=c.

I expect {7/3} meanta = c and b = dI think it is axiomatic rather than provable ... but as ever, it depends on the initial axioms chosen.Bobresearching .....LATER:Looks like it isn't an axiom. hhmmm.So try a-c = i(d-b) => i = (a-c)/d-b) =><= i is not real unless d = b

That is not a true statement.

I can't see any way to solve this prove,a+bi=c+di implies a=b and c=d